2013
DOI: 10.1007/s15010-013-0431-1
|View full text |Cite
|
Sign up to set email alerts
|

A 6-year antifungal stewardship programme in a teaching hospital

Abstract: The implementation of an antifungal stewardship programme was feasible, sustainable and well accepted. We observed an improved quality of care for some process of care measures, and antifungal use and cost were contained in our hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 24 publications
2
57
0
5
Order By: Relevance
“…Our study demonstrates that at the first bedside assessment, a diagnostic suggestion was necessary in 40% of the patients and that therapy had to be modified in 30%. Mondain et al demonstrated that an AFSP based on a complete bundle of measures improved the quality of care in candidemia and invasive aspergillosis and reduced overall mortality (7). Similar results were found by Antworth et al, who implemented a comprehensive care bundle for the management of candidemia in a US hospital.…”
Section: Adequacy Of Antifungal Therapy: Final Evaluationsupporting
confidence: 52%
See 1 more Smart Citation
“…Our study demonstrates that at the first bedside assessment, a diagnostic suggestion was necessary in 40% of the patients and that therapy had to be modified in 30%. Mondain et al demonstrated that an AFSP based on a complete bundle of measures improved the quality of care in candidemia and invasive aspergillosis and reduced overall mortality (7). Similar results were found by Antworth et al, who implemented a comprehensive care bundle for the management of candidemia in a US hospital.…”
Section: Adequacy Of Antifungal Therapy: Final Evaluationsupporting
confidence: 52%
“…Although significant success has been demonstrated with antibacterial stewardship interventions, experience with antifungal drugs is scarce. Some programs include formulary restriction and preauthorization requirements (3)(4)(5) or did not include all available antifungal agents (6)(7)(8). Nowadays, when competition for resources is huge and proof of return on investment a requisite, the cost-effectiveness and safety of antifungal stewardship programs (AFSPs) need to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…conversion (1). Of the 36 included studies, 2 were full CEAs [13,14]; 27 studies reported changes to costs and health outcomes separately [3,5,[8][9][10][12][13][14][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and 9 reported only changes to costs [4,6,[15][16][17][18][19][20][21]. Table 1 presents the methods and results for studies that measured only cost outcomes and Table 2 presents the methods and findings of those studies that measured both a clinical as well as a cost outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Costing studies that did not measure clinical outcomes Table 1 groups 9 of the 36 included studies that measured only the cost impact of AMS strategies [4,6,[15][16][17][18][19][20][21]. PAIF was the most commonly evaluated strategy in this group (5/9; 56%) [4,6,[15][16][17]; 2 studies focused on i.v.-to-p.o.…”
Section: 1mentioning
confidence: 99%
“…[108][109][110] One study reviewed 636 prescriptions, of which 72% were from the adult and pediatric hematology-oncology services, over 6 y. 108 The ASP provided feedback to the primary teams regarding diagnostic investigations, TDM, and antifungal prescribing and found a high compliance rate (88%) with ASP recommendations. Patient outcomes were favorable in 47 of 63 (75%) with IA and 52 of 60 (87%) with IC, and the total cost of antifungals was stable.…”
Section: Evidence For Antifungal Stewardshipmentioning
confidence: 99%